Comparative Study of Safety and Effectiveness Between IV Dexmedetomidine and IV Propofol for Procedural Sedation During Upper GI Endoscopic Interventions - Khola, Zulnoorain; Saeed, Riffat; Mehmood, Tehreem; Anwar, Saadia; Mahmood, Zareen; Chaudhary, Usman; Farooq, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Safe and effective sedation is essential for upper gastrointestinal (GI) endoscopic interventions. Dexmedetomidine and propofol are commonly used agents with distinct pharmacodynamic profiles that may influence recovery time, hemodynamic stability, and complication rates. In resource-constrained healthcare environments such as Pakistan, selecting the optimal sedative is crucial to minimize risks and enhance procedural throughput. Objective: To compare the safety and effectiveness of intravenous dexmedetomidine versus intravenous propofol for procedural sedation during upper GI endoscopic interventions. Methods: A randomized controlled trial was conducted at the Department of Anesthesia, Shaikh Zayed Medical Complex, Lahore, from December 2024 to April 2025. A total of 126 adult patients (ASA I–II) undergoing elective upper GI endoscopy were enrolled using non-probability consecutive sampling and randomized equally into two groups: Group A received IV dexmedetomidine (1 µg/kg loading dose followed by 0.5 µg/kg/h infusion). In contrast, Group B received IV propofol (0.5 mg/kg loading dose followed by 50 µg/kg/min infusion). Standard monitoring was performed, and sedation depth was assessed using the Ramsay Sedation Score. Recovery time was defined as the interval to achieving a Modified Aldrete Score of 10/10. Hemodynamic parameters, adverse events, and need for rescue sedation were recorded. Data were analyzed in SPSS version 25 using independent-samples t-tests and chi-square tests, with p ≤ 0.05 considered statistically significant. Results: Participants had a mean age of 41.9 ± 12.4 years, and 55.6% were male. The dexmedetomidine group required significantly longer to reach a Ramsay Sedation Score of 4 than the propofol group (318 ± 92 vs 192 ± 64 seconds; p < 0.001). However, recovery time was significantly shorter with dexmedetomidine (8.0 ± 3.6 vs 12.4 ± 3.1 minutes; p < 0.001). Hypotension occurred more frequently with propofol (25.4% vs 11.1%; p = 0.038), whereas bradycardia was more common with dexmedetomidine (7.9% vs 0%; p = 0.023). The need for rescue sedation was higher in the dexmedetomidine group (19.0% vs 4.8%; p = 0.013). Rates of oxygen desaturation, nausea, and vomiting were comparable between groups. Conclusion: Dexmedetomidine demonstrated a more favorable safety profile by reducing hypotension and providing significantly faster recovery compared to propofol, though it required more rescue sedation and was associated with higher rates of bradycardia. These findings support the use of dexmedetomidine as an effective and hemodynamically stable alternative for procedural sedation in upper GI endoscopy, particularly in populations with increased cardiovascular risk.